Panoramic and Immersive Media Studies Yearbook (De Gruyter, 2025)
The PIMS Yearbook surveys the historical and contemporary landscape of panoramic and immersive media. This interdisciplinary field includes—but is not limited to—360-degree paintings dioramas and museum displays gaming gardens immersive experience maps material culture studies media archeology 19th-century popular media optical and haptic devices performative media printed matter public history and virtual and augmented reality.